Bank capital forbearance - Natalya Martynova; Enrico C. Perotti; Javier Suárez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
We analyze the strategic interaction between undercapitalized banks and a supervisor who may intervene by preventive recapitalization. Supervisory forbearance emerges because of a commitment problem, reinforced by fiscal costs and constrained capacity. Private incentives to comply are lower when supervisors have lower credibility, especially for highly levered banks. Less credible supervisors (facing higher cost of intervention) end up intervening more banks, yet producing higher forbearance and systemic costs of bank distress. Importantly, when public intervention capacity is constrained, private recapitalization decisions become strategic complements, leading to equilibria with extremely high forbearance and high systemic costs of bank failure.
Keywords: G21; G28; 330; bank supervision; bank recapitalization; forbearance